RETROFITTING A CONVENTIONAL LATHE TO A DIGITAL INTELLIGENCE SYSTEM - Minhat, Mohamad; Sulaiman, Mohd Amri; Kasim, Mohd Shahir (2014)
The development of modern technologies in computer software, hardware, and firmware as well as the integration of these technologies in the industrial lines have proved better and more efficient productions can be machined. In this project, an attempt has been made to equip the conventional lathe machine with Digital Intelligence system (DIS) in order to get more accurate dimensions and precise shape of high end products. The retrofitting process of the conventional lathe machines into semi automatic control lathe machine, demands two key elements, namely, mechanical and electronics parts. In the mechanical part, a design is made to feed the stepper motor to the lead screw. On the other hand, in the electronics part, an electronic circuit containing the motor driver circuit is designed in order to control the motor movement